SISTEM INFORMASI MONITORING ABSENSI SEKOLAH DASAR DENGAN MENGUNAKAN SERVICE ORIENTED ARCHITECTURE - Muhamad Muslih; Cecep kurnia sastradipraja; Reni Rahayu (INFOKOM (Informatika & Komputer), 2022)
The world of education is currently competing to implement technology in the processing of information and communication technology systems to create effectiveness and efficiency. The increasing and developing information and communication technology in educational institutions, the school information system in an elementary school needs to be improved. standardized steps and methods that must be followed to produce a reliable information system. The curriculum information system of schools in primary schools themselves is still using manuals, but the current school information system data processing is still simple, that is still using microsof office computer facilities so that the data is still not neatly arranged and causes delayed report writing because of the difficulty in obtaining information in fast time. Therefore, in this study a school curriculum information system will be built using the service oriented architecture in the elaboration, revealing the output data of this study is the realization of an application that will facilitate the principal, teachers and other staff to carry out the teaching and learning process and report making. which is expected to improve the effectiveness, productivity and improve the quality of the primary school attendance monitoring information system.